The four pillars of scholarly publishing: The future and a foundation - Byrnes, J.; Baskerville, E.; Caron, B.; Neylon, Cameron; Tenopir, C.; Schildhauer, M.; Budden, A.; Aarssen, L.; Lortie, C. (Queen's University, 2014)
© 2014 The Author. © Ideas in Ecology and Evolution 2014.